Proceedings of SPE/PS-CIM/CHOA International Thermal Operations and Heavy Oil Symposium 2005
DOI: 10.2523/97743-ms
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Modeling Integral to Effective Design and Evaluation of SAGD Processes of an Athabasca Oil-Sands Reservoir: A Case Study

Abstract: fax 01-972-952-9435. AbstractThe design and implementation of a successful thermal recovery project starts with a representative static geological model. SAGD operating strategies of the steam chamber for optimum economical oil recovery with minimum SOR are largely controlled by the target reservoir geological and pressure environment. This paper describes how geostatistical modeling techniques were used to build a static reservoir model over a 32-section area of a Fort McMurray oil sand reservoir. The model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Consequently, the starting injection pressure is the formation pressure. In fact, it has been shown categorically that injecting steam at high pressure increases oil production (Kisman and Yeung, 1995;Robinson et al, 2005). However, one other complexity of the injection process is the pressure schemes maintained throughout the lifetime of the wells.…”
Section: Optimization Of Operating Conditions and Well Placement Key mentioning
confidence: 99%
“…Consequently, the starting injection pressure is the formation pressure. In fact, it has been shown categorically that injecting steam at high pressure increases oil production (Kisman and Yeung, 1995;Robinson et al, 2005). However, one other complexity of the injection process is the pressure schemes maintained throughout the lifetime of the wells.…”
Section: Optimization Of Operating Conditions and Well Placement Key mentioning
confidence: 99%
“…They concluded that high pressure SAGD induced higher porosity and permeability with higher oil production. In order to observe the effects of geomechanics variation and hence permeability enhancement due to shear dilation, steam chambers should be operated at or near the minimum total stress, which implies HP-SAGD ( Another study showing favourability of HP-SAGD was conducted by Robinson et al (2005), where they also reported an increase in oil production. Kisman and Yeung (1995) also showed that operating at low pressure decreased oil production and improved OSR in a simulation model for the Burnt Lake oilsands conditions.…”
Section: Length Spacing and Placement Of Horizontal Wellsmentioning
confidence: 99%
“…Thus, one has to pay attention to use representative reservoir models in SAGD performance analyses using numerical simulators as the reservoir heterogeneity may have considerable effects on the accuracy of the process. A good demonstration for such approach is shown by Robinson et al (2005). McLennan and Deutsch (2005) stated that flow modeling is a transfer function converting the geological uncertainty to production uncertainty.…”
Section: Numerical Simulationmentioning
confidence: 99%